The handbook of Chinese linguistics (Malden, MA Chichester, West Sussex, UK : Wiley-Blackwell, 2014)
"Offers a unique, comprehensive introduction to Chinese linguistics from the perspective of modern theoretical and formal linguistics"--
Part I. Syntax, semantics, and morphology -- part II. Phonetics, phonology, and prosody -- part III. Language acquisition and psycholinguistics -- part IV. Historical linguistics -- part V. Morpho-syntax of other non-Mandarin varieties of Chinese.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Chinese language -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Chinese language; Electronic books; Handbooks and manuals